Aerobic exercise combined with environmental enrichment improves spatial memory and enhances neuroligin 1 expression: an animal study (Medical Journal of Indonesia, 2019)
BACKGROUND Numerous studies have revealed that aerobic exercise (AE) or environmental enrichment (EE) exert positive effects on the molecular, cellular, and structural changes responsible for functional plasticity. Therefore, this study was aimed to investigate whether the combination of AE and EE yields a greater effect on spatial memory and increases the expression of the adhesion molecule neuroligin 1 compared with either of the therapies alone. METHODS Twenty 6-month-old male Wistar rats were randomly divided into four groups: (1) the control group (C), (2) the AE group, (3) the EE group, and (4) the AE-EE group. Escape latency in a Water-E-maze (WEM) task was used as a parameter to assess spatial memory function. Neuroligin 1 protein expression was examined via the immunohistochemistry (IHC) technique followed by IHC optical density (OD) score analysis of the CA1 hippocampal region. RESULTS Data acquired from the WEM task show that escape latency progressively decreased over time in all groups. However, animals in the AE-EE group required less time to complete the task compared with those in the control, AE, and EE groups. IHC OD scores revealed that the combination of AE and EE caused the highest expression of neuroligin 1 in the CA1 hippocampal region among the therapies studied. Statistical analysis indicated significant differences in OD score between the AE-EE and control, AE, and EE groups (p ≤ 0.001). CONCLUSIONS The combination of AE and EE rats increased neuroligin 1 expression and improved the spatial memory of male Wistar rats compared with application of either therapy alone.